Mobility of IT professionals in Malaysia - Md Dahalin, Zulkhairi; Sheik Osman, Wan Rozaini; Othman, Nafishah; Mat Aji@Alon, Zahurin; Man, Noraziah; Mat Kasim, Maznah; A. Razak, Hanissah; Che Mit, Daratul Ambia (Universiti Utara Malaysia, 2004)
This paper is based on a research study with the aim to investigate the mobility of IT professionals in Malaysia and come up with suggestions to improve recruitment and retention policies for the IT profession.A questionnaire,namely the IT Professional Turnover/Mobility Survey for the Management of IS/IT Department was constructed and administered to 415 respondents IT employees listed in the Malaysian National Computer Confederation (MNCC) registration list with a 25% response rate.Data gathered were statistically analysed descriptive statistics such as frequency counts and percentages,cross-tabulation,and correlation analysis.A research model was constructed based on review of related articles to determine factors that contribute tomobility of IT professionals.Among the major findings were a large majority of respondents would never or seldom moved and likely to stay for more than five years.Majority of respondents also indicated that they would remain as IT professionals with no plans to change their career.The findings also suggest that the three most attractive factors for moving among IT professionals are better salary,better working condition and better environment.The most common reasons for leaving was not happy with working conditions and no opportunity for self development.Good pay/renumeration was considered the best factor for staying in current organization,location (nearer to home) and career advancement opportunities were the two most popular factors chosen.On mobility factor,the variables found to be significantly related to mobility of IT professionals are: Age, Marital Status and Experience (Demographic Information);Tryout and Travel (Personality factor);Quitting Job and Satisfaction (Job Satisfaction);Salary (Career Advancement); and Work Condition and Flexi Time (Organizational Factor).On the employer's perspektive,the three most critical problems faced by employers when their IT personnel leave were disruption to scheduler,retraining, and difficulty to get replacement.In summary, the findings presented in this study suggest that IT professionals are likely to stay in their professions,felt that they have made the right choice in their career with the intention of staying with their current job,whilst charting their career goals within the IT profession, but less ambitious in taking up a more senior position within or outside the organization.